1987
DOI: 10.1099/00221287-133-8-2191
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the cAMP Level in the Yeast Saccharomyces cerevisiae: Intracellular pH and the Effect of Membrane Depolarizing Compounds

Abstract: Addition of plasma membrane depolarizing agents, such as dinitrophenol (DNP) and azide, to cells of Saccharomyces cerevisiae under aerobic conditions, is known to cause an increase in the cAMP level within 15 s. We found that both compounds lowered the intracellular pH (measured by in vivo 32P-NMR) drastically within the same time period. Plasma membrane depolarization, however, was much slower: DNP and azide had no effect on the membrane potential during, respectively, the first 2 min and the first 10 min aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 13 publications
9
68
0
1
Order By: Relevance
“…Early 31 P NMR studies indicated that yeast intracellular pH was not affected by the external pH conditions or the presence of NH 4 ϩ (41). However, several subsequent studies found that the intracellular pH of yeast followed the external pH when the extracellular medium was either strongly buffered (18,(42)(43)(44) or contained weak organic acids such as acetate, butyrate, or succinate (19,(45)(46)(47). This suggests that the plasma membrane of yeast is permeable not only to NH 4 ϩ but also to other weak acids.…”
Section: Nh 4 ϩ -Mediated Acidification Of the Yeast Vacuolementioning
confidence: 99%
“…Early 31 P NMR studies indicated that yeast intracellular pH was not affected by the external pH conditions or the presence of NH 4 ϩ (41). However, several subsequent studies found that the intracellular pH of yeast followed the external pH when the extracellular medium was either strongly buffered (18,(42)(43)(44) or contained weak organic acids such as acetate, butyrate, or succinate (19,(45)(46)(47). This suggests that the plasma membrane of yeast is permeable not only to NH 4 ϩ but also to other weak acids.…”
Section: Nh 4 ϩ -Mediated Acidification Of the Yeast Vacuolementioning
confidence: 99%
“…For cAMP determination, cells were grown on YP medium supplemented with 3 '/o glycerol and 0.1 % galactose until lateexponential phase. Incubation with glucose and fructose (100 mM each) and quantification of cAMP followed our established protocol (Thevelein et al, 1987). The same culturing regime was used for cells in which the levels of glycolytic metabolites were determined according to Novel yeast hexokinase mutations de Koning & van Dam (1992).…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, only two triggers of the yeast Ras-adenylate cyclase pathway have been identified : glucose and related fermentable sugars (Van der Plaat, 1974;Mbonyi et al, 1988) and intracellular acidification (Thevelein et al, 1987).…”
Section: Introductionmentioning
confidence: 99%